A Fiji multi‐coral δ18O composite approach to obtaining a more accurate reconstruction of the last two‐centuries of the ocean‐climate variability in the South Pacific Convergence Zone region. (18th December 2014) - Dassié, Emilie P.; Linsley, Braddock K.; Corrège, Thierry; Wu, Henry C.; Lemley, Gavin M.; Howe, Steve; Cabioch, Guy
Abstract The limited availability of oceanographic data in the tropical Pacific Ocean prior to the satellite era makes coral‐based climate reconstructions a key tool for extending the instrumental record back in time, thereby providing a much needed test for climate models and projections. We have generated a unique regional network consisting of five Porites coral δ18O time series from different locations in the Fijian archipelago. Our results indicate that using a minimum of three Porites coral δ18O records from Fiji is statistically sufficient to obtain a reliable signal for climate reconstruction, and that application of an approach used in tree ring studies is a suitable tool to determine this number. The coral δ18O composite indicates that while sea surface temperature (SST) variability is the primary driver of seasonal δ18O variability in these Fiji corals, annual average coral δ18O is more closely correlated to sea surface salinity (SSS) as previously reported. Our results highlight the importance of water mass advection in controlling Fiji coral δ18O and salinity variability at interannual and decadal time scales despite being located in the heavy rainfall region of the South Pacific Convergence Zone (SPCZ). The Fiji δ18O composite presents a secular freshening and warming trend since the 1850s coupled with changes in both interannual (IA) and decadal/interdecadal (D/I) variance. The changes in IA and D/I variance suggest a re‐organization of climatic variability in the SPCZ region beginning in the late 1800s to period of a more dominant interannual variability, which could correspond to a southeast expansion of the SPCZ.